VR-based assessment and intervention of cognitive functioning after stroke - Gamito, Pedro (2022)
Worldwide, stroke affects one out of every six individuals, being associated with physical and cognitive impairments, and leaving a striking footprint on individuals, their families and society. Assessment of acquired deficits and rehabilitation of lost and compromised functions is based typically on exercises that may not replicate the demands of everyday life activities lacking ecological validity. These tests fail at predicting daily functioning and their similarity with daily life activities is far from being sound. Assessing and training cognitive functions under an ecologically oriented approach, i.e. using exercises that replicate instrumental activities of daily living (IADL) seems to be the suitable strategy to follow. Virtual Reality (VR) worlds have been used to simulate IADL for assessment and rehabilitation of acquired cognitive deficits since the late 1990’s. This chapter reports and debates existing studies that support the use of VR in this context. When it comes down to veridicality and verisimilitude, evidences illustrate the opportunity of adopting this strategy that outperforms traditional paper and pencil exercises. A glance through the perspective of a therapist, that has adopted VR for cognitive rehabilitation in patients with stroke is also debated.